ChemInform Abstract: Copper(I)‐Catalyzed Sulfonylation of (2‐Alkynylaryl)boronic Acids with DABSO. Issue 40 (16th September 2016) - Mao, Runyu; Zheng, Danqing; Xia, Hongguang; Wu, Jie
Abstract: affording benzothiophene 1, 1‐dioxides